2012
DOI: 10.3762/bjoc.8.249
|View full text |Cite
|
Sign up to set email alerts
|

Highly stereocontrolled synthesis of trans-enediynes via carbocupration of fluoroalkylated diynes

Abstract: SummaryTreatment of readily prepared (Z)-6-benzyloxy-1,1,1,2-tetrafluoro-6-methyl-2-hepten-4-yne with 1.5 equiv of LHMDS in −78 °C for 1 h gave the corresponding trifluoromethylated diyne in an excellent yield. This diyne was found to be a good substrate for the carbocupration with various higher-ordered cyanocuprates to give the corresponding vinylcuprates in a highly regio- and stereoselective manner. The in situ generated vinylcuprates could react very smoothly with an excess amount of iodine, the vinyl iod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…After several trials, we found that the dehydrofluorination of tetrafluorinated enynes 13 proceeded efficiently (Scheme 7). 18 Thus, treatment of 2,3,3,3-tetrafluoro-1-iodo-1-propene (5) with a terminal alkyne (1.2 equiv) and triethylamine (Et 3 N) (1.5 equiv) in the presence of 5 mol% of palladium(II) acetate [Pd(OAc) 2 ] and 10 mol% each of triphenylphosphine…”
Section: Scheme 6 Synthesis Of Cf 3 Propargylamines 10mentioning
confidence: 99%
See 1 more Smart Citation
“…After several trials, we found that the dehydrofluorination of tetrafluorinated enynes 13 proceeded efficiently (Scheme 7). 18 Thus, treatment of 2,3,3,3-tetrafluoro-1-iodo-1-propene (5) with a terminal alkyne (1.2 equiv) and triethylamine (Et 3 N) (1.5 equiv) in the presence of 5 mol% of palladium(II) acetate [Pd(OAc) 2 ] and 10 mol% each of triphenylphosphine…”
Section: Scheme 6 Synthesis Of Cf 3 Propargylamines 10mentioning
confidence: 99%
“…These intermediates reacted smoothly with water, leading to the trisubstituted alkenes 31a in high to excellent yields, whereas they reacted only with limited carbon electrophiles, such as allyl, crotyl, methallyl, and propargyl bromides, but not benzyl bromide, due to the low re- The carbocupration of CF 3 alkynes is also a powerful tool in the stereoselective synthesis of CF 3 -substituted transenediynes, as shown in Scheme 17. 18 Thus, CF 3 -containing diynes 12 reacted smoothly with various higher-ordered cyanocuprates to give the corresponding vinyl copper intermediates. In all cases, the re-actions proceeded in a highly selective cis-addition manner.…”
Section: Scheme 14 Carbocupration Of Various Cf 3 Alkynesmentioning
confidence: 99%